Nutritional profiling and sensory evaluation of hilsa Tenualosa Ilisha (Hamilton, 1822) eggs roe from three different locations of Bangladesh - Muhammad Anamul Kabir; Kamrul Islam; Shishir Kumar Nandi; Sanzida Hoque; El-Sayed Hemdan Eissa; Hien Van Doan; Suniza Anis Mohamad Sukri; Zulhisyam Abdul Kari (Scientific Reports)
Abstract Hilsa (Tenualosa ilisha) eggs roe is considered delicacy food products among consumers and has high potential due to its superior nutrients. This study, conducted in 2023, examined the nutritional profiling and sensory attributes of T. ilisha eggs roe from Cox’s Bazar, Chandpur, and Patuakhali regions in Bangladesh. Majority of the bioimetrical and morphometric parameters were significantly (P < 0.05) varied across distinct areas. The eggs roe proximate composition were significantly (P < 0.05) influenced by different areas. Significant (P < 0.05) variations were found in most of the amino acid contents in Hilsa eggs from distinct locations. Glutamic acid (14.20–14.60%) was the predominant amino acid in all locations, followed by alanine (12.77–13.03%), aspartic acid (8.60–9.50%), and leucine (8.43-9.00%). Among 22 identified fatty acids in Hilsa eggs roe, C16:0 (31.08–32.86%), C18:1n-9 (20.73–22.23%), and C22:6n-3(5.55–5.68%) dominated as major SFA, MUFA, and PUFA, respectively. Significantly (P < 0.05) the highest Σω-3 were detected in the egg’s roe from Patuakhali. The mineral composition showed significant (P < 0.05) differences across diverse locations. The eggs roe from Patuakhali had significantly (P < 0.05) increased taste and appearance. Hence, these findings suggested that eggs roe development from Patuakhali region could be better compared to other area for human health benefit in terms of nutritional point of view.